2014
DOI: 10.1590/s0103-84782014000200025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e distribuição espacial da leishmaniose visceral em cães do município de Juatuba, Minas Gerais, Brasil

Abstract: RESUMO O presente estudo teve como objetivo determinar a prevalência e a distribuição espacial da leishmaniose visceral em cães (LVC) do município de Juatuba, Minas Gerais

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
13

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 9 publications
(4 reference statements)
1
11
0
13
Order By: Relevance
“…Costa et al (2005) evaluated the influence of basic services and sanitation in the city of Teresina in the state of Piauí, Brazil, and determined a higher risk of human infection in areas lacking proper sewage disposal and waste collection. These factors, according to Borges et al (2014), can contribute to the occurrence of canine and human VL. The authors of a study in the city of Juatuba, Minas Gerais, Brazil, observed a disease prevalence of approximately 50% in neighborhoods with deficient sanitation and unpaved streets, characteristics that were also observed in the study area of our work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Costa et al (2005) evaluated the influence of basic services and sanitation in the city of Teresina in the state of Piauí, Brazil, and determined a higher risk of human infection in areas lacking proper sewage disposal and waste collection. These factors, according to Borges et al (2014), can contribute to the occurrence of canine and human VL. The authors of a study in the city of Juatuba, Minas Gerais, Brazil, observed a disease prevalence of approximately 50% in neighborhoods with deficient sanitation and unpaved streets, characteristics that were also observed in the study area of our work.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of knowledge of the transmission dynamics in the area and of the presence of vector and wild reservoirs can contribute to sudden expansion of the disease, in contrast to what occurs in endemic regions (BORGES et al, 2014). The situation seen in Porto Alegre may also be occurring in other cities in Brazil, because road construction and increased air travel is increasing the traffic of people and their domestic animals, which, in turn, increases the risk of dispersion not only of CVL but other infectious diseases as well.…”
Section: Feitosamentioning
confidence: 99%
See 1 more Smart Citation
“…Provavelmente essa elevação se deve ao aumento da disponibilidade das notificações ao SINAN, sendo que a queda nos anos seguintes pode ser explicada pelo fato de no ano de 2010 terem começado as campanhas contra a LV e os seus resultados aparecerem nos anos seguintes 15 . Através dos dados de notificação obtidos pela Vigilância Epidemiológica da cidade de Guanambi pode-se perceber que os bairros com maior incidência de casos de LV foram Monte Pascoal, Ipiranga e Vomitamel, sendo estes bairros localizados na periferia da cidade, onde grande parte dos moradores é advinda de uma classe social baixa, podendo este fator ter influênciasobre 18 o fator da desnutrição, frequente em grupos populacionais de baixa condição socioeconômica e nos quais a doença é prevalente.…”
Section: Sinanunclassified
“…Além disso, a imunidade é uma justificativa para a predileção pela infância, que deve-se ao fato de ser este grupo particularmente susceptível à infecção e à progressão para o estado mórbido por conta da imaturidade do sistema imunológico 4 . Quanto menor a resposta imunológica do paciente, menor será sua resposta terapêutica e maior será o aparecimento de novas infecções 18 . .…”
Section: Sinanunclassified